An Examination of The Government's Failure to Gender Mainstream Affirmation in Banyuwangi Regency, East Java, Indonesia - Hidayati, Emi; Septalinda, Ficky; Fardian, M.Iqbal (Iapa Proceedings Conference, 2024)
One of the global objectives aimed at eradicating gender inequality is gender mainstreaming. The Republic of Indonesia's initial step toward integrating gender mainstreaming into legal products is Presidential Instruction No. 9 from 2000. Affirmation of gender mainstreaming is then transferred to local government. The goal of this study is to examine the institutional dynamics of affirmation of gender mainstreaming in Banyuwangi Regency. The descriptive qualitative method is used in this study, and documentation, interviews, and observation are the methods used to acquire data. From the outset, gender mainstreaming's implementation dynamics and process encountered a number of well-known challenges, including gender blindness, political concerns, and institutional difficulties. This research suggests that theorized government failure results from the adoption of gender mainstreaming affirmation.